Review: Metabolit Sekunder dan Aktivitas Farmakologi Tanaman Mangrove Sonneratia alba - Mairing, Priskila Putri; Ariantari, Ni Putu (Jurnal Farmasi Udayana; Vol. 11, No. 1, Tahun 2022DO - 10.24843/JFU.2022.v11.i01.p01, 2022)
Sonneratia alba is a mangrove species widely distributed in Indonesia and locally known as pidada putih or perepat. Various parts of this plant have been used in folk medicine for the treatment of bruises, sprains, malaria, appendicitis, liver, increased appetite, and stamina. This review summarizes the latest information regarding secondary metabolites and pharmacological activities of extracts and phytochemicals of the mangrove S. alba , potentially used for pharmaceutical and nutritional applications. In the last 10 years (2011-2021), a growing number of reports revealed pharmacological potential of S. alba as antibacterial and antioxidant. At least 17 secondary metabolites have been described from S. alba collected from various plant parts such as fruits, leaves, stems, and roots. In addition, various chemical classes of metabolites such as terpenoids/triterpenoids, alkaloids, flavonoids and phenolics, saponins, and steroids were reported from this plant. Keywords: Pharmacological activity, secondary metabolites, S onneratia alba